Developing accounts receivable accounting information systems for banks retention in real estate companies - Prayogo, Utomo; Widyaningdyah, Agnes Utari (Department of Accounting, Faculty of Business, Universitas PGRI Yogyakarta, 2022)
Real estate companies have this specific retention account receivable due to revenue recognition. The problem was demands to maintain the reliability of receivable balances stated in the balance sheet and to provide comprehensive information on retention receivables for the collection management process. It is necessary to develop an accounting information system for the retention of account receivables at the company. This study aims to develop an Accounting Information system using the waterfall model of the SDLC method. The current system needs to be improved in supporting the reliability of balance sheets and is not yet able to assist in the decision-making process regarding the collection management process. The result of this research is to successfully develop an accounting information system for retention receivables that can produce sufficient, comprehensive reports to support decision-making. It is suggested that system development be implemented in the design of a detailed database and its relation to the existing database and implemented by revising the current software so that it can be integrated with the retention receivables information system.